Color discrimination with broadband photoreceptors. - Schnaitmann, C.; Garbers, C.; Wachtler, T.; Tanimoto, H. (Current Biology, 2013)
Color vision is commonly assumed to rely on photoreceptors tuned to narrow spectral ranges. In the ommatidium of Drosophila, the four types of so-called inner photoreceptors express different narrow-band opsins. In contrast, the outer photoreceptors have a broadband spectral sensitivity and were thought to exclusively mediate achromatic vision.Using computational models and behavioral experiments, we demonstrate that the broadband outer photoreceptors contribute to color vision in Drosophila. The model of opponent processing that includes the opsin of the outer photoreceptors scored the best fit to wavelength discrimination data. To experimentally uncover the contribution of individual photoreceptor types, we restored phototransduction of targeted photoreceptor combinations in a blind mutant. Dichromatic flies with only broadband photoreceptors and one additional receptor type can discriminate different colors, indicating the existence of a specific output comparison of the outer and inner photoreceptors. Furthermore, blocking interneurons postsynaptic to the outer photoreceptors specifically impaired color but not intensity discrimination.Our findings show that receptors with a complex and broad spectral sensitivity can contribute to color vision and reveal that chromatic and achromatic circuits in the fly share common photoreceptors.